2018
DOI: 10.5935/0103-507x.20180059
|View full text |Cite
|
Sign up to set email alerts
|

An electronic warning system helps reduce the time to diagnosis of sepsis

Abstract: ObjectiveTo describe the improvements of an early warning system for the identification of septic patients on the time to diagnosis, antibiotic delivery, and mortality.MethodsThis was an observational cohort study that describes the successive improvements made over a period of 10 years using an early warning system to detect sepsis, including systematic active manual surveillance, electronic alerts via a telephonist, and alerts sent directly to the mobile devices of nurses. For all periods, after an alert was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
10
0
5
Order By: Relevance
“… 10 , 12 , 13 Some of these systems were created for use in the inpatient ward, 14 , 15 intensive care unit (ICU), 16 , 17 and emergency department (ED), 18 , 19 and some stretch across settings within a healthcare system. 20 , 21 One study demonstrated that over 75% of sepsis hospitalizations presented in the ED, warranting a focused study of this population. 22 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 12 , 13 Some of these systems were created for use in the inpatient ward, 14 , 15 intensive care unit (ICU), 16 , 17 and emergency department (ED), 18 , 19 and some stretch across settings within a healthcare system. 20 , 21 One study demonstrated that over 75% of sepsis hospitalizations presented in the ED, warranting a focused study of this population. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Studies (24,27) show that the patient with sepsis has altered physiological parameters 8 hours before, and their survival depends on the ability of the nurse to recognize these changes. It is essential to train the nursing teams, since the nurse is the professional who has the most contact with the patient Therefore, nurses must be able to promptly identify these alterations and act in rapid, safe and well-founded manner.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should also seek to answer several other important questions such as the optimal type of sepsis alert, which team members should be alerted, and at what frequency should they be alerted. A recent observational cohort study reviewing successive improvements over a 10-year period found that reviewed sepsis alerts were sent to a telephonist and alerts were sent to a nurse's mobile phone [42]. They found that time to antibiotics was reduced to 1 hour (55 min to 1 hour 30 min) when the alert was sent to the telephonist and to 45 min (30 min to 1 hour) when the alert was sent directly to the nurse's mobile phone (P=.02) [42].…”
Section: Discussionmentioning
confidence: 99%